Correlation of CD4 and Distal Sensory Polyneuropathy in HivAids Patients - Desti Ariani Kistanti1, Paulus Sugianto1, Erwin Astha Triyono2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Infection of human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) has developed into one of the most important health problems in the world. Distal sensory polyneuropathy (DSP) is the most common complication of peripheral neuropathy in HIV-AIDS. Risk factors associated with DSP are elderly, stage of HIV disease, (cluster differential-4) CD4 count, and high plasma viral load in plasma. To analyze the relationship between CD4 and distal sensory polyneuropathy in HIV-AIDS patients. Subjects of the study examined the degree of severity of distal sensory polyneuropathy by examination of the Surface Nerve Surgical Nerve Speed, then divided into case group and control group. After that, the subjects performed a CD4 count examination. Data analysis using chi-square test. Most body mass index (BMI) subjects did not experience malnutrition by 35% of case group and 35% control group (p = 1.000). Most subjects aged ?40 years were 37.5% of case group and 25% control group (p = 0.102). Analysis of CD4 relation with Speed of Nerve Surgical Nerve Survival was obtained p = 0.038. There was a significant relationship between CD4 and Distal Sensory Polyneuropathy in HIV-AIDS patients. While age and malnutrition were not found a significant relationship with distal sensory polyneuropathy.